The Impact of the Problem-Solving Model in Social Studies Learning on Social Sensitivity of Elementary School Teacher Education Students - Intansari, Ilfi; Haryanto; Erviana, Vera Yuli (Universitas Pendidikan Ganesha, 2022)
Students and students as student statuses should have sensitivity to problems that arise in society, especially those related to their chosen field. This study aims to analyze the effect of problem-solving models on social sensitivity in elementary school teacher education students. This study uses a quantitative descriptive approach. Data was collected using an instrument in the form of a questionnaire. The questionnaire uses a Likert Likert scale of 1-5. Subjects in this study amounted to 61 people. The data analysis process was carried out using multiple linear regression analysis, which was preceded by a prerequisite analysis test. According to the findings of this study, not all proxies of problem-solving skills affect the social problem sensitivity of social studies students. Only focus, reason, situation, and overview affect the sensitivity to social problems, while the inference and clarity variables partially do not affect the problem of social sensitivity. However, simultaneously all of these variables affect the sensitivity to social problems of social studies students. Based on this, it is recommended for further research to examine the components that affect sensitivity to social problems so that other variables that affect sensitivity to social problems can be identified.